PERSONALITY DISORDERS AND THEIR IMPACT ON TREATMENT OUTCOMES: A CLINICAL PSYCHOLOGY PERSPECTIVE - Ahmed Demir; Hale Yilmaz; Azamat Nazarov (Research Psychologie, Orientation et Conseil, 2026)
Personality disorders (PDs) are pervasive mental health conditions that significantly impact an individual's behavior, interpersonal relationships, and overall functioning. These disorders are often associated with complex treatment challenges, as they frequently co-occur with other psychiatric conditions and complicate therapeutic interventions. Understanding the influence of personality disorders on treatment outcomes is crucial for developing more effective, tailored interventions for patients with these conditions. This study aims to explore the impact of personality disorders on treatment outcomes in clinical psychology, focusing on how PDs affect the success of various therapeutic approaches and the therapeutic alliance. The goal is to identify key factors that influence treatment efficacy and highlight strategies to improve outcomes for individuals with PDs. A systematic review and meta-analysis of existing clinical trials and longitudinal studies were conducted. Data were extracted from 30 studies involving over 2,000 participants diagnosed with personality disorders. The analysis focused on treatment modalities such as Cognitive Behavioral Therapy (CBT), Dialectical Behavior Therapy (DBT), and psychodynamic therapy, examining their effectiveness in patients with different types of PDs. The findings indicate that individuals with PDs experience slower and less consistent progress compared to those without PDs, with DBT showing the most significant positive effects. Treatment outcomes were further influenced by the presence of comorbid conditions and the type of PD. Personality disorders significantly affect treatment outcomes, requiring specialized approaches to address their complexities. Tailored interventions such as DBT are recommended to improve efficacy in treating patients with PDs.